Experience, image and architecture. bergson’s way. (2005)
This article deals with Henri Bergson´s thoughts on theexperience of the world, its different moments and therole the notion of image plays in this world. A parallel isestablished between architecture and these concepts anda methodological way is proposed to comprehend a workof architecture. The Ceremonial Plaza of the Simón BolívarPark in Bogotá (designed by Arturo Robledo) isused a case study.